1997
DOI: 10.1128/jb.179.6.1931-1939.1997
|View full text |Cite
|
Sign up to set email alerts
|

sfi-independent filamentation in Escherichia coli Is lexA dependent and requires DNA damage for induction

Abstract: In Escherichia coli, damage to DNA induces the expression of a set of genes known collectively as the SOS response. Part of the SOS response includes genes that repair DNA damage, but another part of the response coordinates DNA replication and septation to prevent untimely cell division. The classic SOS gene product that inhibits cell division is SfiA (or SulA), which binds to FtsZ and prevents septum formation until the DNA damage has been repaired. However, another pathway acts to coordinate DNA replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 45 publications
4
62
0
Order By: Relevance
“…As discussed above, SOS induction, as measured in luceriferase gene fusions (fold induction of SulA promoter 1.76 Ϯ 0.69), did not occur concomitant with ObgE depletion. Both SulA-dependent and SulA-independent filamentation have been observed to depend on RecA gene function (Hill et al, 1997). We found that cell filamentation in ObgE-depleted cells was not dependent on functional RecA.…”
Section: Inefficient Ftsz-ring Formation In Obge-depleted Cellssupporting
confidence: 50%
“…As discussed above, SOS induction, as measured in luceriferase gene fusions (fold induction of SulA promoter 1.76 Ϯ 0.69), did not occur concomitant with ObgE depletion. Both SulA-dependent and SulA-independent filamentation have been observed to depend on RecA gene function (Hill et al, 1997). We found that cell filamentation in ObgE-depleted cells was not dependent on functional RecA.…”
Section: Inefficient Ftsz-ring Formation In Obge-depleted Cellssupporting
confidence: 50%
“…This so-called sfi-independent pathway of cell filamentation is recA dependent (Burton and Holland, 1983;Hill et al, 1997). Since filamentation of the dnaAcos cells occurs independently of the functional recA gene, the CedA-linked pathway found in this work includes, at least, a novel step necessary for septum formation.…”
Section: Discussionmentioning
confidence: 68%
“…Bacteria respond to stresses such as oxidative stress (8), nutrient stress (36), DNA damage (22), and some antibiotics (21,37) by arresting DNA replication and/or cell division. Filamentous uropathogenic Escherichia coli have been observed during infection of bladder epithelial cells (38).…”
Section: Discussionmentioning
confidence: 99%
“…Filamentous bacteria were observed using another Salmonella Typhimurium strain (14028s), indicating that filamentation is shared by more than one strain of Salmonella Typhimurium (data not shown). Filamentous bacteria had partial or absent septa, suggesting a defect in completion of cell division, an indicator of bacterial stress (21,22).…”
Section: Ifn-␥ Priming Of Raw 2647 Cells Restricts Salmonella Typhimmentioning
confidence: 99%